DETERMINATION OF PARASITE DRAG FOR COMMERCIAL AIRPLANE AT TRANSONIC SPEEDS - V. I. Shevyakov (Научный вестник МГТУ ГА)
It considers the task of determination of parasite drag for subsonic commercial airplane on the base of theoretical calculation procedures. It contains the procedure for clarification of empirical approach to calculation of parasite drag at high speeds. It provides examples of calculation of parasite drag at transonic speeds as a result of step behind the slat on the wing of commercial airplane.